Magnesium intake is associated with the metabolically healthy obese phenotype. (March 2022) - Guerrero-Romero, Fernando; Morales-Gurrola, Gerardo; Preza-Rodríguez, Lucía; Gómez-Barrientos, Alejandra; Olivas-Martínez, Ana I; Simental-Mendía, Luis E
Although magnesium intake is inversely associated with the risk of metabolic abnormalities, whether magnesium intake plays a role on metabolically healthy obese (MHO) phenotype has not been explored. Therefore, the purpose of this study was to determine whether the magnesium intake is associated with the MHO phenotype. Apparently, healthy women and men aged 20–65 years with obesity were enrolled in a cross-sectional study. Subjects were allocated into MHO (n=124) and metabolically unhealthy obese (MUO) (n=123) groups. MHO phenotype was defined by abdominal obesity (waist circumference ≥90 cm in men and ≥80 cm in women) and none, or not more than one of the following risk factors: triglyceride levels ≥150 mg/dL; high-density lipoprotein cholesterol (HDL-C) levels <40 mg/dL in men and <50 mg/dL in women; fasting glucose ≥100 mg/dL; and systolic blood pressure ≥130 mm Hg and/or diastolic blood pressure ≥85 mm Hg. The MUO individuals were characterized by abdominal obesity and the presence of two or more of the aforementioned criteria. The proportion of individuals with high blood pressure (40.7% vs 5.6%, p<0.001), hyperglycemia (69.1% vs 16.9%, p<0.001), hypertriglyceridemia (84.6% vs 36.3%, p<0.001), and low HDL-C (51.2% vs 12.9%, p<0.001) was significantly higher in the MUO individuals as compared with individuals in the MHO group. The logistic regression analysis adjusted by sex and age showed that dietary magnesium intake is significantly associated with the MHO phenotype (OR=1.17; 95% CI 1.07 to 1.25, p=0.005). Our results show that magnesium intake is significantly associated with the MHO phenotype.